Clinical and Functional Outcomes of COVID-19 Survivors After Hospitalization - Nazir, Arnengsih; Putri, Salsabila S S; Bashari, Muhammad Hasan (Kesmas, 2023)
Coronavirus disease 2019 (COVID-19) causes various clinical manifestations during acute infection and at the post-acute phase with persistent symptoms called long COVID. It occurs in mild and moderate to severe cases which require hospitalization. In patients needing hospitalization, especially intensive care unit admission, the risk of long COVID increases. Many hospitalized patients exhibited more symptoms in 60 days after the illness than non-hospitalized patients. This review aimed to identify the clinical and functional outcomes in COVID-19 survivors after hospitalization. The articles in the PubMed database published in 2019-2021 were reviewed and found 20 be eligible. The clinical outcomes were the appearance or persistence of general and multi-organ symptoms, nutritional disorders, and decreased lung function. The functional outcomes found were decreased muscle strength, physical, psychological, and cognitive functions, increased disability and dependencies, as well as decreased vocational status and quality of life. The incidence of each outcome could not be determined due to the variety of methods used to examine and present outcomes. To conclude, COVID-19 causes long-term clinical and functional outcomes that need to be identified to prevent and manage long-term physical and functional disorders.